Mineralogical and geochemical constraints on the origin, alteration history and metallogenic significance of the Manganore iron-formation, Northern Cape Province, South Africa - Papadopoulos, Vlassis (Rhodes University, Faculty of Science, Department of Geology, 2017)
The Manganore iron-formation (MIF) of the Transvaal Supergroup is host to the most important high-grade iron ore bodies in South Africa. Prevailing models for ore genesis invoke supergene processes performing during a long period of erosion, oxidation and weathering under tropical lateritic conditions while the role of potential hydrothermal processes is not addressed. Lack of detailed petrographical and geochemical data necessitated reexamination of the MIF through new and existing drill core exploration material. Thorough petrographical investigation revealed a multi-event complex alteration history involving hydrothermal activity. Iron and silica mobility during alteration is demonstrated by a series of replacement, overprinting, crosscutting textures, extensive silicification and hematitization. Metasomatized textures such as pseudomorphs of primary magnetite, carbonate minerals and chert pods/lenses point to an alteration occurring in layer- controlled fronts and link stratigraphically the MIF to Kuruman and Griquatown iron- formations. Whole-rock geochemical data verify textural observations suggesting strong enrichment of iron or silica in meter-scale horizons, expressed by different generations of quartz and hematite. High-grade iron ore is highly enriched in TiO2 and Al2O3 compared to the protolith while both BIF and iron ore display highly increased concentrations of trace elements (transition metals and HFSE). Oxygen isotopes from different quartz textures reveal little to none isotopic exchangement during alteration whereas O isotopes from hematite are in concert to values from literature and suggest two different generations of hematite. A total of 20 minerals apart from quartz and hematite were documented. An earlier alkali/HFSE alteration event that is believed to have affected the overlying Gamagara shales is recorded in the BIF by the presence of muscovite, apatite, rutile, zircon and xenotime. A later and possibly ongoing event of succeeding hydrothermal pulses involves mainly sulphates (gypsum, baryte, celestine), pyrite, carbonates (siderite, calcite) and silicates (berthierine and tourmaline). Alkali-bearing brines persistently exploit the BIF mainly through karstification-related secondary porosity, are evidently carrying iron and are proposed to participate in or control the iron enrichment by facilitating removal of silica. The source of metals, sulfur and carbon is attributed to the underlying Campbellrand dolomites and especially to the upper Gamogaan Formation. The unconformable contact between BIF and the overlying shales is suggested as a suitable fluid conduit for the development of the observed BIF and shale-derived high-grade hematite iron ore.
Keywords: Banded iron formation; Transvaal Supergroup (South Africa); Groups (Stratigraphy) -- South Africa; Lithostratigraphy; Petrology -- South Africa; Geochemistry -- South Africa